PEMETAAN POTENSI WILAYAH HOME INDUSTRY DI KECAMATAN GIRIMARTO KABUPATEN WONOGIRI - Siskak Akatani Kaudsar; Sri Hariyati Fitriasih; Yustina Retno Wahyu Utami (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2020)
Some residents in Girimarto sub-district make industrial businesses their main source of livelihood. The lack of information about the home industry in the Girimarto District area results in a less than optimal marketing of industrial products and the sale of products produced only around Wonogiri Regency. In addition, the inequality in the provision of facilities from the government has resulted in the very slow development of home industries.Based on these problems, an application will be made system geographic informality mapping the potential of a home industry in the District of Girimarto to provide information on existing home industries and grouping data using a Fuzzy tahani  model database modeling to provide the results of classification of home industry data based on variable number of production per year, number of workers and the amount of turnover per year. The results of this system classification / grouping of home industry data in accordance with selected criteria with the highest fire strength value 1 from (interval 0-1). Hopefully this application can help provide information to the public about the home industry in the District of Girimarto and be able to classify home industry data so that it can be used as a decision-making material in how to develop the industry.